الشائعات وسبل مكافحتها في عالمنا المعاصر من خلال منهج النبي ص في التعامل معها - دراسة وصفية- - مومني, رزيقة (University of Eloued جامعة الوادي, 2017)
تتناول هذه الدراسة موضوع الشائعات، وهي الأخبار التي تنتشر في المجتمع من غير تثبت من صحتها, حيث تعتبر هذه الظاهرة من أخطر الأمراض التي تعاني منها المجتمعات منذ القدم, لما لها من آثار سلبية على بناء المجتمع, لأنها تتعلق بمختلف مجالات الحياة السياسية والاجتماعية والاقتصادية والدينية. وهي تمسّ جميع الأفراد وعلى مختلف الأصعدة والمستويات سواء البسيطة كالأسرة والأصدقاء والجيران.. أو الكبيرة كسائر المجتمع المدني ووسائل الإعلام المختلفة. وأخطارها هي التي تكون على مستوى المجتمع الدولي. وحيث تُعد الشائعات اليوم أهم أسلحة الحرب النفسية الأكثر استخداما, أين يستغلها البعض لتحقيق أهدافه ومصالحه في إخضاع الشعوب لسيطرته لا بقوة السلاح لكن بقوة الكلمة وغزو العقول. وباعتبار أن الغرب هو المتفوق في هذا المجال, فإن هدفه الأول ولا شك هو ضرب الإسلام والمسلمين. ولهذا جاءت هذه الدراسة بهدف الكشف على أبعاد الشائعات النفسية والاجتماعية. والأغراض والدوافع وراء نشرها, وكذلك الآثار المترتبة عنها, وبيان موقف الشريعة الإسلامية منها. والتعرف على التوجيه الرباني والنبوي في معالجة مشكلة الشائعات وسبل مكافحتها في عالمنا المعاصر, وذلك من خلال استعراض بعض الشائعات التي راجت في صدر الإسلام بدراسة وتحليل وقائعها وكيفية تعامل النبي  معها, ثم محاولة استنباط المنهج القويم في مكافحة الشائعات من خلال عمل النبي  ومواقفه معها, والذي يمكن إسقاطه وتوظيفه في واقع المسلمين المعاصر في ظل ما يتعرض له الإسلام من حملات تشويه وبث الشائعات المسمومة, التي أرهقت كاهل الأمة الإسلامية وجعلتها تتخبط في متاهات وصراعات شغلتها وأبعدتها عن الدور الريادي الذي وجدت من أجله وهو حمل رسالة الإسلام إلى العالم. ولهذا فمن أهم أسباب التي أدت إلى اختياري هذا الموضوع، هو عدم التزام كثير من المسلمين اليوم بأخلاقيات الإسلام والآداب الشرعية في مجال نشر الإشاعة وترديدها، ولعل ذلك يكون من جهل منهم بخطورة مايفعلونه. وغفلة جمهور المسلمين وعدم مبالاتهم تجاه مخططات الأعداء رغم أنها تستهدف وجودهم نفسه، وذلك لعدم التزامهم بمنهج سليم في التعامل مع الشائعات موافقا لمنظور الإسلامي. وقد وبيّن هذا البحث، أن الإشاعة تلعب دورا كبيرا في التأثير على الروح المعنوية للفرد ونشر الفرقة والكراهية بين أفراد المجتمع. وأن موقف الشريعة الإسلامية من الإشاعات موقف واضح سليم، فهي تقف موقفا حازما ورافضا ومحذرا من نشرها بين صفوف المسلمين، كما يوجه الإسلام إلى الأساليب الناجعة في التحصين والوقاية منها This study deals with the subject of rumors, which are spreading in society without proven authenticity. This phenomenon is considered one of the most serious diseases afflicting societies since ancient times because of its negative effects on the building of society, because it relates to various areas of political, social, economic and religious life .. It affects all individuals and at various levels and levels, such as simple family, friends and neighbors .. Or as large as the rest of civil society and the various media .. The most serious are at the level of the international community. Where rumor is today the most important weapons of psychological warfare, where used by some to achieve its goals and interests in subjecting people to control to keep arms but the power of the word and the invasion of minds. As the West is superior in this area, its first objective is undoubtedly to hit Islam and Muslims. Hence, this study aims to uncover the dimensions of psychological and social rumors, the purposes and motives behind their publication, as well as the implications thereof, and the position of the Islamic Shari'ah. And to identify the guidance of the Lord and the Prophet in dealing with the problem of rumors and ways to combat them in the modern world, and by reviewing some of the rumors that circulated in the beginning of Islam to study and analyze the facts and how the Prophet dealt with them, and then try to devise the correct approach in the fight against rumors through the work of the Prophet and his positions with it , Which can be dropped and employed in the reality of contemporary Muslims in light of what is subjected to Islam campaigns of distortion and broadcast poisonous rumors, which burdened the Islamic nation and made them wandering in the mazes and conflicts filled and away from the leading role that was found for it is to carry the message of Islam to the world did not. Therefore, one of the most important reasons that led to the choice of this subject is the lack of commitment of many Muslims today the ethics of Islam and the legal ethics in the area of spreading the rumor and echo, and this may be ignorance of the seriousness of what they do. And the indifference of the Muslim public and indifference towards the schemes of the enemies, although they target their own existence, because of their lack of commitment to a sound approach in dealing with rumors in accordance with the perspective of Islam. This research has shown that rumor plays a major role in influencing one's morale and spreading disunity and hatred among members of society. And that the position of the Islamic Sharia of rumors is a clear position sound, it stands firm and rejecting and warning of its publication among the Muslims, and Islam is directed to effective methods of immunization and prevention
مذكرة ماستر تخصص دعوة واعلام
Keywords: الشائعات – المنهج – الإرجاف – الشريعة الإسلامية – النفاق; Rumors - curriculum - Irjaf - Islamic law - hypocrisy